Arteriovenous malformation associated with trauma: A case report - Girardi, Adriana; Prestes Valente, Amanda; Alex Longhi, Joel; Paz Portinho, Ciro; Belle Manfroi Galinatti, Clara; Ventura Gomes Júnior, Sérgio; Helson Russowsky Herter, Arthur; Morello, Emerson (Clinical and Biomedical Research, 2015)
A 28-year-old male patient presented to our vascular surgery service with a large, pulsating, slowly progressive mass located in the left buttock. He had a history of a blunt trauma in the same region 6 years ago. Physical examination revealed a firm mass with about 10 cm in major diameter.